Imaging with extended depth of field by means of the peacock eye optical element - Torres, Walter; Barrera, John F.; Henao, Rodrigo; Jaroszewicz, Zbigniew; Kakarenko, Karol; Mira-Agudelo, Alejandro; Petelczyc, Krzysztof; Sypek, Maciej; Kołodziejczyk, Andrzej (Photonics Letters of Poland, 2017)
The paper presents imaging properties of the peacock eye optical element. Its abilities for imaging with extended depth of field is illustrated experimentally in monochromatic as well as polychromatic light. According to the obtained results the element makes possible to maintain the acceptable resolution, contrast and brightness of the output images for a wide range of defocusing. Full Text: PDF References J. Ares, R. Flores, S. Bara, and Z. Jaroszewicz, "Presbyopia Compensation with a Quartic Axicon", Optom. Vis. Sci. 82, 107 (2005). CrossRef G.-m. Dai, "Optical surface optimization for the correction of presbyopia", Appl. Opt. 45, 4184 (2006). CrossRef Z. Liu, A. Flores, M. R. Wang, and J. J. Yang, "Diffractive infrared lens with extended depth of focus", Opt. Eng. 46, 018002 (1-9) (2007). CrossRef E. E. Garcia-Guerrero, E. R. Mendez, H. M. Escamilla, T. A. Leskova, and A. A. Maradudin, "Design and fabrication of random phase diffusers for extending the depth of focus", Opt. Express 15, 910 (2007). CrossRef J. Lin, J. Liu, J. Ye, and S. Liu, "Design of microlenses with long focal depth based on the general focal length function", J. Opt. Soc. Am. A 24, 1747 (2007). CrossRef N. Davidson, A. A. Friesem, and E. Hasman, "Holographic axilens: high resolution and long focal depth", Opt. Lett. 16, 523 (1991). CrossRef A. Kołodziejczyk, S. Bara, Z. Jaroszewicz, and M. Sypek, "The Light Sword Optical Element?a New Diffraction Structure with Extended Depth of Focus", J. Mod. Opt. 37, 1283 (1990). CrossRef K. Petelczyc, S. Bará, A. Ciro Lopez, Z. Jaroszewicz, K. Kakarenko, A. Kolodziejczyk, and M. Sypek, "Imaging properties of the light sword optical element used as a contact lens in a presbyopic eye model", Opt. Express 19, 25602 (2011). CrossRef K. Kakarenko, I. Ducin, K. Grabowiecki, Z. Jaroszewicz, A. Kolodziejczyk, A. Mira-Agudelo, K. Petelczyc, A. Składowska, M. Sypek, "Assessment of imaging with extended depth-of-field by means of the light sword lens in terms of visual acuity scale", Biomed Opt Express 6, 1738 (2015). CrossRef Z. Jaroszewicz, A. Kołodziejczyk, D. Mouriz, and J. Sochacki, "Generalized Zone Plates Focusing Light into Arbitrary Line Segments", J. Mod. Opt. 40, 601 (1993). CrossRef L. A. Romero, M. S. Millían, Z. Jaroszewicz, A. Kolodziejczyk, "Double peacock eye optical element for extended focal depth imaging with ophthalmic applications", J. Biomed. Opt. 17 046013 (2012). CrossRef